Paper versus Screen: Impact on Reading Comprehension and Speed - Ely Shuhadah Tajuddin; Fitri Suraya Mohamad (Indonesian Journal of Education Methods Development, 2019)
Choosing the appropriate reading format is important for students to achieve effective reading. This quasi-experimental study investigates the effects of paper versus screen on reading comprehension and speed among undergraduate students who are currently enrolled in a public university in Sarawak. The general objective of this study is to investigate the formats for effective reading and comprehension among undergraduates. Instruments that have been used in this study were a set of questionnaires, a set of general interest articles, corresponding comprehension questions, and an online timer. Findings revealed that students tended to have better reading comprehension when reading on the screen. Conversely, students were able to read faster using the paper format. Data also revealed that there is significant difference between paper and screen formats for both reading comprehension and reading speed.